Contact screening and management in a high-transmission MDR-TB setting in Papua New Guinea: Progress, challenges and future directions - Majumdar, Suman S.; Islam, Shahidul; Huang, G. Khai Lin; Morris, Lucy; Bauri, Mathias; Chan, Geoff; Kama, Gabriel; Keam, Tess; Peacock-Smith, Abby; Finch, Stacia; Marukutira, Tafireyi; Bhatt, Shivani; et al. (Frontiers in Tropical Diseases, 2023)
Daru, South Fly District, Papua New Guinea is a high transmission setting for multidrug-resistant tuberculosis (MDR-TB). An emergency response by the Government in 2014 established a high-quality model for treatment and care. Household contact screening and management commenced in 2016 with TB preventive treatment (TPT) for well young child (<5 years) contacts of people with drug-susceptible TB and later expanded to young child contacts of MDR-TB. The model of care is community-based and led by non-specialist health workers, under supervision. An electronic medical record system supports care, reporting and operational research. Community engagement and education has been central, with a concerted focus on peer-led counselling and patient-centred services to improve TPT uptake and completion. Challenges include the application of households as the unit of intervention for detection of active TB and TPT provision. Our implementation experience in Daru has highlighted significant population mixing dynamics with most transmission likely occurring outside the household. We propose a community-wide screening approach with the provision of TPT based on testing to include older children, adolescents, and young adults. As there is the possibility of MDR-TB infection irrespective of the drug susceptibility of the household index case, a novel option is a combination TPT regimen of 6 months of daily isoniazid and levofloxacin (6HLfx). A sensitive aged-related algorithm to detect and exclude active TB is being developed. Ongoing community engagement, quality data systems with operational research to evaluate approaches are critical in high transmission MDR-TB settings.